Chikungunya: Diagnostic, Treatment and Challenge in Indonesia - Ali Ramzi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Chikungunya based on the literature is classified as one of the many diseases that become a differential diagnosis of acute undifferentiated fever. Finally, patients with this condition are treated with empirical therapy so that often the management does not meet the standards / undertreatment. In an effort to reduce morbidity and improve the quality of care with limited modalities, history taking and physical examination as well as effective risk factor analysis are necessary in the current situation in Indonesia. Therefore, the authors raise this topic to help improve diagnostic acuity and the importance of the role of laboratory modalities in the diagnosis of chikungunya in Indonesia. Google Scholar by using the search keywords